Anatomopathological lesions produced by prolonged doses of phenylbutazone in a race horse - Choez A., Katherine (2017)
The present paper describes the case of a two-year-old filly who developed severe gastrointestinal lesions after receiving prolonged doses of phenylbutazone when treating a fracture in the right forelimb. Necropsy findings revealed severe acute diffuse catarrahhemorrhagic-ulcerative gastritis and submucosal edema and severe diffuse acute mucohemorrhagic enterocolitis and splenomegaly with severe acute passive congestion. The cause of death was due to cardio-respiratory arrest and coagulopathy with circulatory disturbance and gastric ulcerogenic process associated with iatrogenic shock by phenylbutazone.